Political Empowerment of European Citizens. A Comparative Public Opinion and Approach - Alaminos Chica, Antonio; Perea Crespo, Ignacia (SocietàMutamentoPolitica, 2017)
Over time, the European Union has undergone a number of highly significant integration processes on an economic, social and political level. With the structure of States, it has implemented a number of actions aimed at empowering citizens by harmonising different rights and producing relevant processes in first-generation political rights. Through the EU members’ public opinion, this article analyses the effects of European foreign migrants’ electoral rights in both local and European elections. With the analysis of the data from the 2010, 2012 and 2015 European barometers, it is concluded that there is a relation between the presence of European migrants and the opinion of the electoral effect, as well a significant relation between the existing subjective perception of political empowerment, the opinion on the effects of these rights with regard to political participation and the wish to extend these electoral rights for other elections.